2003
DOI: 10.1007/s00421-002-0789-8
|View full text |Cite
|
Sign up to set email alerts
|

Normo- and hypobaric hypoxia: are there any physiological differences?

Abstract: Since Bert (1878) and Barcroft (1925), studies on hypoxia are realized by lowering ambient O(2) partial pressure (PO(2)) either by barometric pressure reduction (hypobaric hypoxia HH) or by lowering the O(2) fraction (normobaric hypoxia NH). Today, a question is still debated: "are there any physiological differences between HH and NH for the same ambient PO(2)?" Since published studies are scarce and controversial, we submitted 18 subjects in a random order to a 40-min HH test and to a 40-min NH test at an am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
211
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(237 citation statements)
references
References 11 publications
(17 reference statements)
25
211
1
Order By: Relevance
“…Loeppky et al, 1997;Savourey et al, 2003), it could be argued that the present results might not be representative of those expected in a hypobaric hypoxic setting. However, a previous study has shown that the hand CIVD responses are similar in normobaric and hypobaric hypoxia (Meeuwsen et al, 2009).…”
Section: Methodological Considerationscontrasting
confidence: 65%
“…Loeppky et al, 1997;Savourey et al, 2003), it could be argued that the present results might not be representative of those expected in a hypobaric hypoxic setting. However, a previous study has shown that the hand CIVD responses are similar in normobaric and hypobaric hypoxia (Meeuwsen et al, 2009).…”
Section: Methodological Considerationscontrasting
confidence: 65%
“…Normobaric hypoxia, in comparison to hypobaric hypoxia, represents a different challenge to ventilation and cardiac autonomic control (5,27,28). For example, increased breathing frequency with a lower tidal volume, higher end-tidal O 2 and CO 2 fractions, and a higher heart rate have been shown when hypobaric hypoxia is compared to normobaric hypoxia (27).…”
Section: Discussionmentioning
confidence: 99%
“…Normobaric hypoxia, in comparison to hypobaric hypoxia, represents a different challenge to ventilation and cardiac autonomic control (5,27,28). For example, increased breathing frequency with a lower tidal volume, higher end-tidal O 2 and CO 2 fractions, and a higher heart rate have been shown when hypobaric hypoxia is compared to normobaric hypoxia (27). To date there are no data on whether hypobaric hypoxia affects the distribution of heart beats throughout the ventilatory cycle, or whether any changes in this distribution affects ventilatory efficiency when exposed to low ambient PO 2 .A further technical limitation was that in the present study, isocapnia may not have been maintained during the hypoxia trial.…”
Section: Discussionmentioning
confidence: 99%
“…These physiological differences could be the result of an increase in dead space ventilation, probably related to reduced barometric pressure in hypobaric hypoxia. 38 Another research showed that some variables of heart rate variability were affected in …”
Section: Normobaric Versus Hypobaric Hypoxiamentioning
confidence: 99%